Congenital multiple arthrogryposis in bovine - Vrisman, D. P. [UNESP]; Bonato, D. V.; Taira, A. R.; Thomaz, E. R.; Peres, J. A.; Malta, C. A. S.; Cintra, C. A.; Cunha, M. S.; Coutinho, L. N.; Crivellenti, L. Z.; Magalhaes, G. M.; Teixiera, P. P. M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2017)
This report describes an anal atresia, anatomical urethra alteration (slightly caudal to the udder), thickened joints, and changes in the pelvis in a newborn Holstein cow. Visualization of the final portion of the rectum was not possible by perineal access and laparotomy through the right flank was performed in order for abdominal exploration and colostomy attempt. During the surgical procedure visceral rupture and malformations incompatible with life were observed, so surgeons opted for euthanasia and necropsy. Alterations were confirmed in the genitourinary and gastrointestinal tract. The non-formation of the anus caused dilation of the distal portion of the rectum with fecal content retention, which was drained to the body of the uterus, with the presence of meconium. This amount of anatomical and clinical changes were diagnosed as congenital multiple arthrogryposis.
Keywords: anal atresia; environmental contaminants; genitourinary malformations; fetal monstrosity